Personification in cecimpedan: the semantic structure of the tradition of balinese children - Arnawa, Nengah (Opción, 2019)
This research aims to provide linguistic analysis of the Balineselanguage characteristics in cecimpedan. The analysis is based on thetheory of semantic structure. The research data was collected fromaudio-visual recordings, a book of Balinese proverbs, traditional artperformances scene, children's pop songs, and informants. Based onthe analysis, the characteristics of the Balinese language incecimpedan are as follows. As a result, the reasoning of inductive anddeclarative analogy is the mental activity that dominates theparticipants in macecimpedan activity. In conclusion, the use ofpersonification is a grammatical demand centered on verbs.